Assessing visitor responses to Luke Jerram’s Gaia installation in Lincoln Cathedral: prayers and well wishes for the world - Brown, Nick (Journal of beliefs and values, 2025)
For six days during the period that Lincoln Cathedral hosted Luke Jerram’s installation, Gaia, visitors were invited to reflect on the world and to write on postcards prayers and well wishes for the world. Analysis of the content of 112 postcards demonstrated that the installation stirred people to reflect on things that really mattered to them. Seven main themes were identified, four concerning vulnerability and three concerning faith and values. The world is vulnerable to conflict and war, vulnerable to degradation, vulnerable to loss of biodiversity, and vulnerable to unhappiness. Faith and values were reflected in awareness of the ephemeral nature of human life, a reminder of God’s presence, and a call for respectful living.